2019
DOI: 10.1128/aac.01510-19
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a Novel 1,3-Beta- d -Glucan Synthase Inhibitor, Ibrexafungerp (Formerly SCY-078), against Candida glabrata

Abstract: Ibrexafungerp (formerly SCY-078), a novel glucan synthase inhibitor with oral availability, was evaluated for activity against Candida glabrata. The susceptibility of clinical strains to ibrexafungerp was determined by microdilution and time-kill assays. The MIC range against wild-type strains was 1 to 2 μg/ml. Ibrexafungerp was also active against the majority of echinocandin-resistant strains. Time-kill studies showed 4- to 6-log-unit reductions in growth at 24 and 48 h with concentrations of 0.25 to 4 μg/ml. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Potent fungicidal activity has been demonstrated with ibrexafungerp in various Candida spp [27,34,37,49]. In a timekill study, ibrexafungerp demonstrated fungicidal activity (≥3-log reduction in cfu/mL) at 24 hours.…”
Section: Microbiologymentioning
confidence: 98%
See 2 more Smart Citations
“…Potent fungicidal activity has been demonstrated with ibrexafungerp in various Candida spp [27,34,37,49]. In a timekill study, ibrexafungerp demonstrated fungicidal activity (≥3-log reduction in cfu/mL) at 24 hours.…”
Section: Microbiologymentioning
confidence: 98%
“…However, ibrexafungerp, the first representative of the 'fungerp' family of compounds, is a structurally distinct triterpenoid glucan synthase inhibitor as compared to echinocandins and interacts differently with the target cell ( Figure 1) [25]. Thus, ibrexafungerp demonstrates in vitro activity against a broad range of Candida isolates with fks1 and fks2 point mutations that cause echinocandin resistance among C. glabrata, C. auris, and Aspergillus spp [26][27][28][29][30][31][32][33][34][35].…”
Section: Ibrexafungerpmentioning
confidence: 99%
See 1 more Smart Citation
“…Ibrexafungerp demonstrates broad in vitro activity against a range of Aspergillus spp. isolates and Candida isolates, including C. glabrata and C. auris, which exhibit fks1 and fks2 point mutations associated with resistance to echinocandin antifungals [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Among Candida species with reduced fluconazole susceptibility, including C. glabrata, C. krusei, C. tropicalis , and C. parapsilosis , MIC 50 ranges with ibrexafungerp were 0.125–1 μg/mL, 0.5–1 μg/mL, <0.03–1 μg/mL, and 0.25–1 μg/mL, respectively.…”
Section: Ibrexafungerpmentioning
confidence: 99%
“…Despite sharing the same drug target with echinocandins, IBX exerts its antifungal activity in a way both overlapping with and distinct from what has been uncovered for echinocandin drugs (16). This underlying mechanism explains the finding that IBX has potent activities against not only the wild-type (WT) Candida species but strains carrying fks mutations that confer resistance to echinocandins (12,14,17,18). IBX also differs from echinocandins, which are intravenous (i.v.…”
mentioning
confidence: 98%